1998
DOI: 10.1016/s1010-7940(98)00222-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-endothelial cells modulation in diabetic patients undergoing coronary artery bypass grafting

Abstract: These results indicate that diabetes mellitus is associated with an increased neutrophil-endothelial cell adhesion probably mediated by the CD1 1b/CD18 molecule; this, in turn, might be responsible for the increased risk of postoperative complications observed in diabetic patients undergoing coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Enhanced vesiculation of leukocyte could account for the result, as shown by increased levels of CD45-and CD66-b-positive microparticles in these patients. Consistent with the involvement of neutrophil activation, several studies have reported upregulation of adhesion molecules on neutrophil from diabetic patients (34,35).…”
Section: Diabetes Vol 51 September 2002mentioning
confidence: 57%
“…Enhanced vesiculation of leukocyte could account for the result, as shown by increased levels of CD45-and CD66-b-positive microparticles in these patients. Consistent with the involvement of neutrophil activation, several studies have reported upregulation of adhesion molecules on neutrophil from diabetic patients (34,35).…”
Section: Diabetes Vol 51 September 2002mentioning
confidence: 57%
“…Previous studies have shown that glucose may contribute to the increased monocyte adherence to endothelium in diabetes (25)(26)(27)(28). It has been proposed that the effect of glucose on monocyte adhesion may occur via mechanisms involving the upregulation of endothelial and/or leukocyte adhesion molecules (25,26,28,51,52), the activation of NF-B, and the generation of ROS (27). Our results showing that blockade of LOX-1 completely abolished glucose-induced monocyte adhesion to endothelial cells demonstrate a new role for LOX-1-mediator of the stimulatory effect of glucose on monocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of MAC‐1 can be caused by acute hyperglycemia, and might result from impaired neutrophil actin polymerization. It was observed that elevated expression of MAC‐1 could contribute to the pathogenesis of diabetic complications by enhancing adhesion between neutrophils and endothelial cells.…”
Section: Neutrophil‐derived Effector Molecules and Type 1 Diabetesmentioning
confidence: 99%
“…It was observed that elevated expression of MAC-1 could contribute to the pathogenesis of diabetic complications by enhancing adhesion between neutrophils and endothelial cells 54,55 .…”
Section: Adhesion Moleculesmentioning
confidence: 99%